"If They Do Not Fulfill What They Have Promised, I Will Accuse Them": Locating Indigenous Women and Their Influence in the California Missions. Issue 3 (17th May 2020) - Rizzo, Martin
Abstract: In Indigenous California, women often held important roles of political and spiritual leadership. Spanish Franciscan colonialism imposed a patriarchal framework through the California missions. Through a close look of the lives of two Indigenous women who lived at Mission Santa Cruz, this article examines how Native women maintained power and influence within the mission communities. The stories of these two women, Yaquenonsat and Yuñan, intersect with difficult issues of rape and sexual violence, infanticide, sterility, abortion, and the impact of sexually transmitted disease. And yet, the article focuses on resistance and expressions of power—the two women played key roles in organizing and planning the assassination of the abusive Padre Quintana in 1812. This article proposes new methodological approaches to the chancery archives to trace the lives of these women and suggests new ways of analyzing stories of individuals and families within the missions to find the subtle ways of resistance and rebellion by Indigenous men and women.